Evaluation of the use of Ancistrus brevipinnis (Loricariidae) as a bioindicator of water quality in the Ilha river, RS, Brazil - Burghausen, Jorge Henrique; Rodrigues, Gabriela Zimmermann Prado; Staudt, Luciane Beatris Mentges; Kayser, Juliana Machado; Souza, Mateus Santos de; Borba, Diulliane de Jesus; Postai, Arthur; Stumm, Ana Júlia; Schneider, Anelise; Linden, Rafael; Gehlen, Günther (Acta Scientiarum. Biological Sciences, 2023)
The use of fish as bioindicators of the effect of contaminants in the aquatic environment is usual. However, detritivorous species are less used for environmental monitoring. Thus, the aim of this study was to evaluate the use of Ancistrus brevipinnis as a potential bioindicator of water quality of the Ilha River, RS (southern Brazil) and compared to the result obtained for a routine species (Bryconamericus iheringii). For this purpose, the condition factor (CF), the presence of morphological changes in the gills and the quantification of metals in different tissues of the specimens collected in three sites of the Ilha River were evaluated. A homogeneity in the distribution of data was observed in the CF for the species B. iheringii, whereas the specimens of A. brevipinnis showed an oscillation in the distribution of data of the CF. Histological analysis showed greater sensitivity of B. iheringii in reproducing characteristics of the environment in its gill lamellae, which was not observed in A. brevipinnis. Conversely, Cr quantification was higher in the intestine samples of A. brevipinnis at all sites and in all collections due to its feeding behavior. The data reinforce the use of water column species as Bryconamericus iheringii for environmental monitoring, even if they do not reflect the whole aquatic ecosystem. Further studies evaluating other tissues and biomarkers, such as the gastrointestinal tract, may assist in describing the use of species more related to sediment.